The effect of 25 days HiHiLo on iron metabolism and Hb in female juvenile low hemoglobin athletes - Xu, Y.; Hu, Y.; Tian, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: This paper aims to observe the effect of living high, and high exercise training on iron metabolism and hemoglobin (Hb) level in juvenile anemic female athletes. Findings will provide evidence for the therapy of sports anemia or low hemoglobin. Methods Fourteen low hemoglobin athletes were randomly assigned to a hypoxic-group (HG,n=6) and a controlgroup (CG,n=8). There were no significant differences between both groups before the experiment in age, weight, Hb, and serum ferritin levels. In the experiment, the HG lived at simulated altitude of 2500m every night (11h/day) and trained at 50m above sea level for 25 days. In addition, they trained on an ergometer three times per week with an intensity of about 70%VO2max for 21 minutes in hypoxia (2500m). The CG lived and trained at 50m above sea level. They also trained three times a week on an ergometer with an intensity of about 80% VO2max for 21 minutes in normoxia. Serum iron, serum ferritin, serum transferrin receptor, total iron binding capacity and Hb were measured before and after the experiment which lasted for 25 days. Results Pre- and post- experiment, the HG increased Hb, SI and TIBC levels significantly (p<0.05) and decreased SF significantly (p<0.05), whereas there were no changes for the CG. There existed heavy iron deficiency between the two groups pre- and post-experiment. The iron deficiency in HG was larger after the experiment. Discussion / Conclusions Twenty five days of simulated 2500m HiHiLo living and training increased the Hb synthesis in low hemoglobin athletes effectively, improving iron absorption, transportation and utilization, but the degree of the iron deficiency was larger.